‘Looking before and after’: Can simple eye tracking patterns distinguish poetic from prosaic texts? - Corcoran, Rhiannon; de Bezenac, Christophe; Davis, Philip (Frontiers in Psychology, 2023)
The study of texts that can be described as ‘serious’ literature has recently been developed within the emerging field of neurocognitive poetics that applies cognitive neuroscientific techniques to examine how we understand and appreciate poetry. The current research used eye-tracking techniques on a small sample of young adults in a proof-of-concept study to see if and how the reading of short, 4-line pieces of poetry differed from the reading of matched prosaic texts, with a particular focus on eye-tracking evidence of the need to reappraise the material as shown in dwell times and regressions (returns to particular places) back and forth within the text. In this two-by-two experimental design it was found that poetic pieces compared to prosaic pieces were associated with longer dwell times and more regressive eye scanning, indicative of a need to re-appraise meaning. This was particularly the case when a need to re-appraise was explicitly built into the final line of the short texts. No significant correlations were found between self-reported literary familiarity and eye tracking patterns. Despite limitations, this proof-of-concept study provides insights into reading patterns that can help to define objectively the nature of literary material. Future research using these, and other psychophysiological metrics, can begin to unpack the putative cognitive and emotional benefits of reading literary material.